Storytelling #2 with Jens Lyberth & Max Ireland - Lyberth, Jens; Ireland, Max; Bouchard, Heather (Canadian Plains Research Centre, 1983)
12 p. transcript of an interview with Jens Lyberth and Max Ireland conducted by [unknown interviewer] on August 17, 1983. Tape number IH-OT.040, transcript disc 124. Consists of an interview that tells of an Inuit death story; a Lillooet (West coast Indian) creation myth; and an account of a man's search for his lost brother. Note: Heather Bouchard, transcriber. Other no